The modest outcome of clinical trials with bone marrow cells for myocardial repair: is the autologous source of cells the prime culprit? - Shahid, Muhammad Siddique; Lasheen, Wael; Haider, Khawaja Husnain (Journal of Thoracic Disease, 2016)
Re-entry of cardiomyocytes into cell cycle and participation of the resident cardiac stem cells (CSCs) as part of the intrinsic repair process have been evidenced in the ischemic heart (1-3). Nevertheless, the inadequacy of these mechanisms of intrinsic repair necessitates outside intervention especially when the damage inflicted is massive in terms of the loss of functional myocytes. The situation is further aggravated by the advanced age of the patients with ischemic heart disease, and the complexity of the disease process which renders the tissue environment in the diseased heart more intimidating for the transplanted cells besides impacting the stemness characteristics and reparability of the intrinsically available stem cells (4).